KERJASAMA EKONOMI AMERIKA SERIKAT DAN INDIA PASCA QUANTITATIVE EASING TAHUN 2008-2012 - Habibullah Alhaqqi; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This paper is a study of economy policy that America takes in response to face up the crisis “Supreme Mortgage” which is caused by bankruptcy of the central bank due to lowering interest rates at the lowest level, and it used by companies to build and sell homes to middle-class people who do not have adequate collateral to get housing loans, the impact arises when a lot of bad credit directly impacts the bankruptcy of several financial institutions. Quantitative Easing was created as a form of anticipation of the supreme mortgage crisis that occurred in America. This policy has a significant impact on countries that have economic relations that are close to America such as India.This study uses a liberal perspective which is then supported by the theory of international cooperation. In international cooperation, an economic policy created by a country can affect the economic situation in other countries. The Quantitative Easing policy conducted by America as a solution to the situation of the Supreme Mortgage crisis in America also has an impact on the economic situation in India as one of the countries that has strong economic cooperation relations with America.The American Quantitative Easing policy is to overcome the Supreme Mortagage crisis. This policy is a monetary policy issued by a central bank, where the central bank pumps money into banks and financial institutions below it to encourage them to lend as much money. Initially the implementation of this policy caused debate because it was feared that it would affect the condition of the world economy, but it turned out that this policy had a positive influence on the Indian state as one of America's partners KeyWords: Policy, Quantitative Easing, Supreme Mortgage,America, Crisis, India,central bank.